1490 Intubation success in prehospital emergency anaesthesia: a retrospective observational analysis of the Inter-Changeable Operator Model (ICOM). Issue 12 (22nd November 2022) - Price, James; Lachowycz, Kate; Steel, Alistair; Moncur, Lyle; Major, Rob; Barnard, Ed
Abstract : Aims, Objectives and Background: Pre-Hospital emergency anaesthesia (PHEA) is a complex procedure with significant risks. First-pass intubation success (FPS) is recommended as a quality indicator in pre-hospital advanced airway management. Previous data demonstrating significantly lower FPS by non-physicians does not distinguish between non-physicians operating in isolation or within physician teams. In several UK HEMS, the role of the intubating provider is interchangeable between the physician and critical care paramedic – termed the Inter-Changeable Operator Model (ICOM). The objectives of this study were to compare first-pass intubation success rate between physicians and critical care paramedics (CCP) in a large regional, multi-organisational dataset of trauma PHEA patients, and to report the application of the ICOM. Method and Design: A retrospective observational study of consecutive trauma patients ≥16 years old who underwent PHEA at two different ICOM Helicopter Emergency Medical Services in the East of England, 2015–2020. Data are presented as number (percentage) and median [inter-quartile range]. Fisher's exact test was used to compare proportions, reported as odds ratio (OR (95% confidence interval, 95%CI)), p-value. Results and Conclusion: In the study period, 13, 654 patients were attended. 674 (4.9%) trauma patients ≥16 years old who underwent PHEA were included in the final analysis: the median age was 44 [28–63] years old, and 502 (74.5%) were male. There was no significant difference in the FPS rate between physicians and CCPs – 90.2% and 87.4% respectively, OR 1.3 (95%CI 0.7–2.5), p=0.38. The cumulative first, second, third, and fourth-pass intubation success rates were 89.6%, 98.7%, 99.7%, and 100%. Patients who had a physician-operated initial intubation attempt weighed more and had a higher heart rate, compared to those who had a CCP-operated initial attempt. In an ICOM setting, we demonstrated 100% intubation success in adult trauma patients undergoing PHEA. There was no significant difference in first-pass intubation success between physicians and CCPs.